Implementasi Media “Recycle Ranger” dengan Nilai Kepramukaan untuk Meningkatkan Motivasi Belajar Siswa SDN Karangpakis 2 - Titah Eka Finanda; Ika Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning activities in the IPAS subject at SDN Karangpakis 2 initially showed low student motivation because the media used were still conventional and lacked interactivity. This condition made it difficult for teachers to capture students’ attention, strengthen engagement, and build the environmental awareness required in project-based learning. This study aims to examine the improvement in learning motivation after implementing the digital educational media Recycle Ranger, which incorporates scouting values into its features. The research employed a mixed-methods approach with a sequential explanatory design involving 26 fourth-grade students. Data were obtained through pretest–posttest motivation questionnaires, observations student participation, and semi-structured interviews with teachers and students. The findings show a significant increase in motivation, reflected in the rise of the average questionnaire score from 61,42 to 75,73. Observational data and interview results reinforce this improvement, revealing that students became more active, enthusiastic, confident, and cooperative during the learning process. The integration of scouting values within the recycling project also helped develop discipline, responsibility, creativity, and teamwork. Teachers noted that the learning atmosphere felt more meaningful because students engaged directly in hands-on activities that supported real understanding. Suggestions include digitizing features, adding missions, and expanding to other classes.